Digitalisierung und Soziale Arbeit Transformationen und Herausforderungen - Wunder, Maik (Verlag Julius Klinkhardt, 2021)
Digitisation now encompasses all functional areas of society and it is hard to imagine life without it. Technical artefacts are becoming increasingly networked and form, among other things, an (invisible) background with which human actions are implicitly and explicitly interwoven in many ways. This volume takes a critical look at (possible) transformations and challenges that arise for social work in the face of socio-technical change. Old questions, such as that of social inequality, gain new contours. At the same time, new problem constellations appear on the horizon of questions, such as the substitution of human professional action by Big Data. The contributions collected in this volume attempt to bridge the gap between theory and practice and between discipline and profession.